Constant low-to-moderate mechanical asymmetries during a treadmill graded exercise test. Issue 4 (3rd April 2022) - Girard, Olivier; Alsenoy, Ken Van; Li, Siu Nam; Ryu, Joong Hyun; Peeling, Peter
ABSTRACT: This study describes asymmetry in key mechanical variables during a treadmill-based, running graded exercise test (GXT). Twenty-one recreationally trained male runners completed a continuous, maximal GXT on an instrumented treadmill, starting at 9 km.h −1 with speed increases of +0.5 km.h −1 every 30 s, for the determination of ventilatory threshold (VT), respiratory compensation point (RCP), and maximal oxygen uptake (MAX). Ground reaction forces were recorded continuously and subsequently averaged from 10 consecutive steps corresponding to VT, RCP and MAX intensity stages (13.4 ± 1.2 km.h −1, 16.0 ± 1.6 km.h −1 and 18.2 ± 1.5 km.h −1, respectively). Asymmetry scores were assessed from the "symmetry angle" (SA) formulae, where a score of 0%/100% indicates perfect symmetry/asymmetry; these were then compared between the three intensity stages. There was no influence of exercise intensity on SA scores for any of the sixteen biomechanical variables ( P  > 0.222). The group mean SA scores did not exceed 1.5% for spatio-temporal variables (contact time, aerial time, frequency and step length). There were larger mean SA scores for mean loading rate (3.7 ± 2.7%) and most spring-mass model variables (vertical stiffness: 2.2 ± 1.6% and leg stiffness: 1.7 ± 1.4%). The SA scores were ∼1.0–3.5% for braking and propulsive phase durations, peak forces, and resulting impulses. Lower extremities behave similarly at submaximal and maximal intensities during GXT, indicating that runners maintained relatively even strides as intensity increased. However, practitioners must be careful not to infer the presence of asymmetry during GXT based on a single variable, given the lower SA scores for spatio-temporal parameters. Highlights Our comprehensive list of sixteen mechanical variables provides a mechanical norm of expected asymmetry during treadmill graded exercise testing for recreationally trained runners. The stride pattern across submaximal and maximal exercise intensities remains consistent between limbs, with mechanical asymmetries being more individual-specific than intensity stage-dependent. Low to moderate asymmetry is a natural phenomenon in recreationally trained runners during treadmill graded exercise testing; notwithstanding, asymmetry scores appear inconsistent between mechanical parameters.